Penambahan Beta-Karoten Alami Pada Pakan Terhadap Performa Ikan Maru (Channa marulioides) - Sri Warastuti; Rizal Akbar Hutagalung; Farid Mudlofar; Maryana Maryana (Faculty of Science and Technology University Ibrahimy, 2022)
Beta carotene is a type of carotenoid that is important for fish health and growth. This study aims to determine the impact of the use of natural beta carotene in the form of carrot flour, sweet potato flour and shrimp head flour on the performance of absolute length growth rate, absolute weight and survival of maru fish. This experiment was designed with a completely randomized design (CRD) consisting of four treatments and three replications. The treatment used different sources of beta carotene as raw material in feed: carrot flour (A); sweet potato flour (B); shrimp head flour (C); and commercial pellet feed as control (K). The results showed that during the 90 days of rearing, the addition of natural beta carotene as raw materials in feed can affect the growth rate, both absolute length growth rate and absolute weight where the addition of shrimp head flour as a natural source of beta carotene can increase the absolute length growth rate and absolute weight growth compared with the treatment using carrot flour and sweet potato flour addition in fish feed. Meanwhile, the difference in the source of beta carotene in the feed was not significantly different and did not affect the survival rate in the rearing of maru fish.